Reduction Kinetics Of Magnetite Concentrate Particles With H2 + Co At 1200 To 1600 °C Relevant To A Novel Ironmaking Process - Mohamed Elzohiery; Yousef Mohassab; Jagannath Pal; Shengqin Zhang; Hong Yong Sohn (The Minerals, Metals and Materials Society, 2016)
The kinetics of magnetite reduction with mixtures of hydrogen and CO of various compositions has been investigated as part of the development of a flash ironmaking process at the University of Utah. This new process bypasses the cokemaking and pelletization or sintering steps required for the blast furnace. The particle kinetics were studied using magnetite concentrate particles of different sizes. Reduction degree of 60% was achieved in a few seconds in at 1350 oC using CO reductant alone and over 90% when H2 + CO gas mixture was used. The effects of reductant partial pressures, temperature, and particle size on the reduction kinetics were studied.